Identification of digallated and methylated catechins using UPLC/MS/MS and development of a rapid analysis method for theanine in tea (Camellia sinensis (L.) O. Kuntze) utilizing evaporative light scattering detection - Apostolides, Zeno (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2009.